Pengembangan teknologi tangki pintar sebagai sistem peringatan dini bencana kekeringan - Adhy Kurniawan; Galih Setyawan; Pratama Tirza Surya Sembada; Geradus Nieken Sabian (Jurnal Teknosains, 2023)
According to the National Disaster Management Agency, in 2021 there were 5,402 incidents recorded, one of them being drought disasters. During the drought, the availability of clean water was minimal, so clean water assistance came from other areas. The problem that is often encountered in the field is delays in water distribution assistance due to sudden information and the location of the aid is in areas that are difficult to reach. This research developed a water tank technology equipped with a sensor to provide information about water availability, the location of the tank placement to speed up information on dropping water in drought areas. This technology uses the NodeMCU ESP8266 module which functions as a microcontroller, to provide sensor-based information that detects the quantity and quality of water as well as the location of the tank. This system is based on the Internet of Things (IoT) and Blynk Android which makes it easier for people to get information in real time. The water availability indicator is presented in a three-color graphical display, namely green is a safe sign (sufficient water), yellow is a warning sign (water is reduced), and red is a sign that water availability is running low and it is necessary to drop clean water. Other information presented is water quality parameters such as pH, TDS, turbidity, and temperature as well as the location of the tank. This technology supports the achievement of SDGs, namely goals number 6 (clean water and proper sanitation) and 11 (sustainable cities and settlements).